1979
DOI: 10.1128/iai.25.1.39-47.1979
|View full text |Cite
|
Sign up to set email alerts
|

Immunological behavior after mycobacterial infection in selected lines of mice with high or low antibody responses

Abstract: Resistance and susceptibility to mycobacterial infection in the Biozzi high and low lines of mice which were genetically selected for their responses to heterologous erythrocytes have been found to be related to the innate ability of nonimmune macrophages to kill or inhibit the growth of the organisms during the first two weeks after infection and to their ability to mount specific and nonspecific immune responses. High antibody-producer mice were more capable of expressing cell-mediated immune parameters than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Upon inhalation by the host, M. tuberculosis primarily targets the alveoli, which is captured by innate immune cells via pattern recognition receptors [14, 74]. The activation of these cells then triggers the host's nonspecific immune response to eliminate the invading mycobacteria [75]. Our results demonstrate that the C624P vaccine significantly increases the population of macrophages, dendritic cells, and NK cells following three rounds of injections.…”
Section: Discussionmentioning
confidence: 95%
“…Upon inhalation by the host, M. tuberculosis primarily targets the alveoli, which is captured by innate immune cells via pattern recognition receptors [14, 74]. The activation of these cells then triggers the host's nonspecific immune response to eliminate the invading mycobacteria [75]. Our results demonstrate that the C624P vaccine significantly increases the population of macrophages, dendritic cells, and NK cells following three rounds of injections.…”
Section: Discussionmentioning
confidence: 95%
“…Lagrange et al (19) indicated that H mice, Selection I, were more resistant to virulent M. tuberculosis than L mice and were effectively protected after BCG vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the inefficiency of the destruction mechanism, the infected macrophage starts to release substances to attract T lymphocytes to the infection site, through the major histocompatibility complex (MHC), class II, at the same time that it displays immunogenic epitopes (proteins and polysaccharides) on its surface. Stimulated T lymphocytes then produce lymphokines, like interferon-γ (INF-γ), that enhance macrophage efficiency during enzymatic digestion by releasing NO, a potent antimicrobial agent (2,12,14,19,21).…”
Section: Introductionmentioning
confidence: 99%
“…lepruemurium in macrophages assisted the immune response in mice (Closs, 1975;. Similarly, mice bred for high antibody production mount a more efficient immune response, and control better a challenge with virulent H37 Rv tubercle bacilli, than do low antibody producers (Lagrange, Hurtel and Thickstun, 1979). There was, however, another difference between the two experiments, and that was that in the preformed complex lesions the antibody was purely specific.…”
Section: Discussionmentioning
confidence: 99%